Dhikr Tariqah Naqsyabandiyah as a Method of Formation of Spiritual Strengthening of Tahfidz Santri at Miftahul Khoir Al-Azhar Islamic Boarding School - Arman Maulana (International Journal of Science Education and Technology Management, 2022)
In principle, the qualitative data analysis is carried out simultaneously with the data analysis process. Data processing can be done through qualitative research, observation, interviews, and documentation. The analysis technique is carried out by including data reduction, data presentation, and drawing or levers. The conclusion is that the Naqsyabandiyah Dhikr Tariqah is a form of process of increasing spiritual value for its adherents which in this case is called Siswa, with the entry of a student into the tarekat along with the spiritual guidance given by murshid to students, therein lies the process of spiritual guidance for students, so that students are always guided which in the end will appear a positive impact will change the values ​​of spirituality in a student. The Koran itself emphasizes the values ​​of good morality (al-Akhlak al-Karimah), the process of reforming the soul in this case through dhikr, where dhikr is part of the commands in the Koran which in the mention is not small. or repeatedly, even in the Koran itself states that dhikr is a way to get peace of mind, from this peace of soul is the core goal of intimate people.